Structural Microangiopathies in Skeletal Muscle Related to Systemic Vascular Pathologies in Humans - Baum, Oliver; Bernd, Jonathan; Becker, Samuel; Odriozola, Adolfo; Zuber, Benoît; Tschanz, Stefan A.; Zakrzewicz, Andreas; Egginton, Stuart; Berkholz, Janine (Frontiers in Physiology, 2020)
It is unclear how microangiopathic changes in skeletal muscle vary among systemic vascular pathologies. We therefore analyzed the capillary fine structure in skeletal muscle from patients with arterial hypertension (HYPT), diabetes mellitus type 2 (T2DM) or intermittent claudication - peripheral arterial disease (IC/PAD). Tablet-based image analysis (TBIA) was carried out to largely re-evaluate 5,000 transmission electron micrographs of capillaries from 126 vastus lateralis biopsies of 75 individuals (HYPT, T2DM or IC/PAD patients as well as healthy individuals before and after endurance exercise training) used in previous morphometric studies, but assessed using stereological counting grids of different sizes. Serial block-face scanning electron microscopy (SBFSEM) of mouse skeletal muscle was used for validation of the particular fine structural events observed in human biopsies. The peri-capillary basement membrane (BM) was 38.5% and 45.5% thicker (P<0.05) in T2DM and IC/PAD patients than in the other groups. A 17.7%-39.6% lower (P<0.05) index for intraluminal endothelial cell (EC) surface enlargement by projections was exclusively found in T2DM patients by TBIA morphometry. The proportion of capillaries with disrupted BM between pericytes (PC) and EC was higher (P<0.05) in HYPT (33.2%) and T2DM (38.7%) patients than in the control group. Empty EC-sockets were more frequent (P<0.05) in the three patient groups (20.6% in HYPT, 27.1% in T2DM, 30.0% in IC/PAD) than in the healthy individuals. SBFSEM confirmed that EC-sockets may exhibit close proximity to the capillary lumen. Our comparative morphometric analysis demonstrated that structural arrangement of skeletal muscle capillaries is more affected in T2DM than in HYPT and IC/PAD, although some similar elements of remodelling were found. The increased frequency of empty EC-sockets in the three patient groups indicates that the PC-EC interaction is commonly disturbed in these systemic vascular pathologies.